Gullies mitigation and control measures: A case study of the Seirós gullies (North of Portugal) - Martins, Bruno Manuel dos Santos de Castro (2019)
It is known that the erosion process triggered by gullies contributes to significant soil loss and land degradation, and this can limit the options for the occupation and development of a territory in terms of the suitability and quality of the farmland area. The variety of physical factors associated with gully formation hinders straightforward interpretations and requires well-grounded analysis based on local observation. This work presents an example of gullies formed in a colluvial hill-slope agricultural area in Seirós, North of Portugal. The gullies were formed by intense rainfall events in 2015 that led to a channel overflowing. The channel in question was 49 m long, 0.50 m wide and 0.50 m deep and had been built by the landowner to protect his farmland from hillslope drainage. The adequacy of the strategy implemented to prevent gully formation with a view to the rehabilitation of the area is validated.